Prevalence of Absence of Palmaris Longus in Students of a Medical College in Nepal - Manandhar, Prabina; Sintakala, Chandan (Journal of Lumbini Medical College, 2021)
Introduction: Palmaris longus is one of the most variable muscles present in the superficial layer of the anterior compartment of forearm and is phylo-genetically categorized as retrogressive muscle. It arises from the medial epicondyle of humerus and forms a long slender tendon which becomes flattened in palm to form palmar aponeurosis and helps in the flexion of hand at wrist. This muscle can be used in plastic surgery or reconstructive surgeries. The present study was carried out to find the prevalence of presence or absence of palmaris longus tendon in Nepalese population so that it would be helpful to provide a baseline data for surgeons to perform surgical procedures.Methods: This was a cross-sectional descriptive study conducted among  200 medical students after the approval from Institutional Review Committee. The presence or absence of tendon of palmaris longus was observed and confirmed on the flexor aspect of wrist by using Schaffer’s test and Thompson’s test.Results: The overall absence of palmaris longus was observed in 55 students (27.5%) with the prevalence of bilateral absence in 27 students (13.5%) and unilateral absence in 28 students (14.0%).The overall absence of palmaris longus was reported in 20 males (23.2%) and in 35 females (30.7%).Conclusion: Absence of palmaris longus (either unilateral or bilateral) was observed in about one fourth of the participants.